2011
DOI: 10.1371/journal.pone.0021507
|View full text |Cite
|
Sign up to set email alerts
|

New Structural and Functional Contexts of the Dx[DN]xDG Linear Motif: Insights into Evolution of Calcium-Binding Proteins

Abstract: Binding of calcium ions (Ca2+) to proteins can have profound effects on their structure and function. Common roles of calcium binding include structure stabilization and regulation of activity. It is known that diverse families – EF-hands being one of at least twelve – use a Dx[DN]xDG linear motif to bind calcium in near-identical fashion. Here, four novel structural contexts for the motif are described. Existing experimental data for one of them, a thermophilic archaeal subtilisin, demonstrate for the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 92 publications
(125 reference statements)
3
61
0
Order By: Relevance
“…EF-hand usually form a helix-loop-helix structure (Day et al, 2002;Derbyshire et al, 2007;Rigden et al, 2011). However, there are some b-propeller structure proteins shown to possess Ca 2+ binding activity (Cioci et al, 2006).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…EF-hand usually form a helix-loop-helix structure (Day et al, 2002;Derbyshire et al, 2007;Rigden et al, 2011). However, there are some b-propeller structure proteins shown to possess Ca 2+ binding activity (Cioci et al, 2006).…”
Section: +mentioning
confidence: 99%
“…Many Ca 2+ sensors contain domain E and F (EF)-hand domains for Ca 2+ binding (Snedden and Fromm, 1998). The typical EF-hand is a helix-loop-helix structure, in which the residues with +X*+Y*+Z*-Y*-X**-Z are associated with Ca 2+ binding (Day et al, 2002;Derbyshire et al, 2007;Rigden et al, 2011). In addition, other motifs such as helix-loopstrand, helix-loop-turn, strand-loop-helix, strand-loopstrand, and several structural contexts without regular secondary structure elements either before or after the DxDxDG-containing loop can provide affinity for binding Ca 2+ (Rigden and Galperin, 2004).…”
mentioning
confidence: 99%
“…These domains are usually expressed in multiple repeats in a-integrin proteins, assembled into a b-propeller structure (4). It has been suggested that most FG-GAP domains contain calcium-binding propeller blades that regulate the folding, activation status, and heterodimerization of integrins, and presumably affect ligand binding (47)(48)(49). Indeed, the second FG-GAP domain of Iftg2 contains the sequence Dx[DN]xDG (aa 134-139), which is the consensus sequence of such calcium blades (48).…”
Section: What Pathways Can Contribute To Itfg2 Function?mentioning
confidence: 99%
“…It has been suggested that most FG-GAP domains contain calcium-binding propeller blades that regulate the folding, activation status, and heterodimerization of integrins, and presumably affect ligand binding (47)(48)(49). Indeed, the second FG-GAP domain of Iftg2 contains the sequence Dx[DN]xDG (aa 134-139), which is the consensus sequence of such calcium blades (48). However, our data showed that Itfg2 is an intracellular protein; therefore, it cannot be directly involved in extracellular ligand binding like the majority of cellsurface a-integrin molecules.…”
Section: What Pathways Can Contribute To Itfg2 Function?mentioning
confidence: 99%
See 1 more Smart Citation